Implementation of PT Pupuk Kujang's Social Innovation in Community Empowerment through Agriculture, Animal Husbandry, Women's Empowerment, and Urban Farming - Agung Gustiawan; Ade Cahya Kurniawan (Prospect Publishing, 2025)
Social innovation is an essential strategy to address various social, economic, and environmental challenges by optimizing local potential in a sustainable manner. This article aims to describe the implementation of social innovation carried out by PT Pupuk Kujang through its Corporate Social and Environmental Responsibility (TJSL) program, which actively involves community participation. The method applied was participatory action research, consisting of needs mapping, planning, implementation, mentoring, and evaluation. Four key programs were analyzed, namely Kuwatan Sadesa, which increased coffee productivity from 1.2 tons/ha toward an optimal potential of 3 tons/ha while conserving forests; Kujang Wanita Tangguh (KUWAT), which empowered women by producing at least two products from garment waste; Asa Warga Ternak Mandiri (Asatama), which developed at least 16 sheep under a communal farming system supported by crowdfunding and the use of pineapple waste as feed; and Kujang Urban Farming (KURFA), which established one greenhouse, engaged ≥10 residents, and generated derivative food products. The results indicate that PT Pupuk Kujang’s social innovation successfully enhanced community welfare, strengthened social solidarity, and promoted environmental sustainability. These achievements highlight the potential of social innovation as a replicable model to be applied in other regions to support sustainable development.